2013
DOI: 10.1021/om4008295
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Chemoselective, Zr-Catalyzed C–O Bond Functionalization of Benzofuran

Abstract: The chemoselective C−O bond functionalization of benzofuran with an aluminum dihydride may be catalyzed by zirconocene dichlorides. The reaction proceeds with the formal addition of a C−O bond to, and elimination of dihydrogen from, aluminum. The product of C−O bond alumination reacts with benzaldehyde via insertion of the carbonyl into the newly formed Al−C bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…1) were capable of the dearomatisation and ring-expansion of benzofuran using a zirconocene catalyst and t-butylethylene as a hydrogen-acceptor. 16 We later showed that the efficiency of this reaction could be improved using [Pd(PCy 3 ) 2 ] in the place of the zirconium catalyst. In both the non-catalysed and catalysed processes, the aluminium reagent (either 1 or 2) inserts selectively into one of the sp 2 C-O bonds of the 5-membered ring of benzofuran.…”
Section: Introductionmentioning
confidence: 99%
“…1) were capable of the dearomatisation and ring-expansion of benzofuran using a zirconocene catalyst and t-butylethylene as a hydrogen-acceptor. 16 We later showed that the efficiency of this reaction could be improved using [Pd(PCy 3 ) 2 ] in the place of the zirconium catalyst. In both the non-catalysed and catalysed processes, the aluminium reagent (either 1 or 2) inserts selectively into one of the sp 2 C-O bonds of the 5-membered ring of benzofuran.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). 5 , 6 In the case of fluorocarbons two competing pathways are observed: hydrodefluorination and C–F alumination. 5 …”
mentioning
confidence: 99%
“…From a mechanistic perspective, these data highlight the possibility that an in situ transition metal catalysed Al( iii ) → Al( i ) transformation may be operating in our previously reported bond functionalisation chemistry employing the Al( iii ) dihydride 1 . 5 , 6 From a more pragmatic point of view, the reactions result in the generation of a new carbon–aluminium bond from ‘inert’ carbon–fluorine or carbon–oxygen bonds. This approach represents a method for directly generating reactive intermediates from non-reactive chemical feedstocks, that uses the most abundant metal in the earth's crust without the need for expensive or toxic transition metal catalysts.…”
mentioning
confidence: 99%
“…In 2013, we demonstrated that aluminium(III) hydride reagents (2) were capable of the dearomatisation and ring-expansion of benzofuran using a zirconocene catalyst and t-butylethylene as a hydrogen-acceptor. 16 We later showed that the efficiency of this reaction could be improved using [Pd(PCy 3 ) 2 ] in the place of the zirconium catalyst. In both the non-catalysed and catalysed processes, the aluminium reagent (either 1 or 2) inserts selectively into one of the sp 2 C-O bonds of the 5-membered ring of benzofuran.…”
Section: Introductionmentioning
confidence: 99%